Pengaruh Model Pembelajaran Project Based Learning (PjBL) Terhadap Aktivitas Belajar Peserta Didik Materi Sistem Reproduksi Kelas XI SMAN 9 Gowa (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to test the significant influence of learning activities of students who are taught using the Project Based Learning learning model of the reproductive system material of class XI SMAN 9 Gowa. This study is a quasi-experimental design with a research design in the form of a Non-equivalent Control Group Design. The population of this study involved all students of class XI MIA SMAN 9 Gowa totaling 210 people. The sample of this study is class XI MIA 3 which totals 35 students as the control class and class XI MIA 4 which totals 35 students as the experimental class. The sampling technique used is purposive sampling. The data collection tool in this study uses observation sheets of student learning activities and documentation. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis with independent sample t-test. The results of the analysis showed that the sign value was less than 0.05, so the hypothesis in this study H1 was accepted and H0 was rejected, because 0.000 < of 0.05. This means that there is a significant influence on the learning activities of students who gain learning by applying the PjBL learning model to the reproductive system material of class XI SMAN 9 Gowa